Hindrances to adaptation to water insecurity under climate variability in peri-urban Ghana - Benebere, Patrick (Cogent social sciences, 2017)
Water insecurity is a development challenge confronting households in the Wa municipality. This paper outlines the hindrances to climate variability adaptation to water insecurity among peri-urban residents within the Wa Municipality. A sample of 345 households was randomly selected from seven communities together with a staff from the Community Water and Sanitation Agency (CWSA) for interviews. The data were analyzed using the statistical tools embedded in the Statistical Product for Services Solution software. Results indicate that climate variability is the main contributing factor to water insecurity in the study area. Hindrances to adaptation to water insecurity include the cost of obtaining water, time spent and distance travelled to obtain water, low literacy levels, income poverty and language barriers to direct translation of climate terminology. The paper recommends that the Municipal Assembly in collaboration with Non-governmental organizations should provide alternative water sources in addition to rainwater for the people in the area.